(untitled) (African Journal of Biomedical Research, 2020)
Hearing loss in children often inhibits speech and language development, thus affecting academic performance, social and emotional well-being. Thus a comparative cross-sectional study was conducted in three primary schools in Ghana to assess hearing of the children attending those schools and also compare differences between these schools based on the pupils’ socioeconomic backgrounds. The data was used to determine prevalence of hearing loss in the schools. A comparison was then made between the results obtained among children attending the more affluent school and the less affluent schools. A total of 773 pupils were included in this study even though 839 pupils were screened as some pupils failed to adequately complete the questionnaires. The average age was 10 years with a standard deviation of 2.65. Significant hearing loss was identified in 4 children (0.5%). Abnormal tympanometry was identified in 86 (10.2%). Abnormal otologic findings identified included cerumen impaction in 73 children (36.5%), acute otitis externa in 7, acute otitis media in 6 and foreign bodies in 10. Schools with lower socioeconomic pupils had a higher prevalence of abnormal tympanometry but there was no difference in hearing loss prevalence. In conclusion, unidentified hearing loss in the three basic schools in Ghana was uncommon and prevalence was not impacted by the school’s socioeconomic background. However, a significant portion had abnormal middle ear function or external auditory canal occlusion from cerumen impaction and thus required further management.